Volume 5C: Heat Transfer 2014
DOI: 10.1115/gt2014-27174
|View full text |Cite
|
Sign up to set email alerts
|

Flow in a Rotating Cavity With Axial Throughflow at Engine Representative Conditions

Abstract: The prediction of compressor drum cavity heat transfer is an important factor in the overall design of an aero engine. The rotationally dominated flow field within the cavity governs the heat transfer conditions by suppressing the motion of the fluid. Without heating, the fluid in the outer region of the cavity can approach solid body rotation. The outer cavity fluid is disturbed by the bore flow at the inner radius. The resultant bore flow vortex has been shown to exhibit many different modes of behaviour, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 0 publications
1
68
0
Order By: Relevance
“…The results also show that the value of N is not only a function of a/b but there are other parameters such as the axial and rotational Reynolds numbers that should be considered. The unsteady and unstable nature of the flow structure within the cavity was also observed and stated by various researchers including [ (Atkins & Kanjirakkad, 2014), (King , et al, 2005), (Tian, et al, 2004)].…”
Section: Numerical Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…The results also show that the value of N is not only a function of a/b but there are other parameters such as the axial and rotational Reynolds numbers that should be considered. The unsteady and unstable nature of the flow structure within the cavity was also observed and stated by various researchers including [ (Atkins & Kanjirakkad, 2014), (King , et al, 2005), (Tian, et al, 2004)].…”
Section: Numerical Resultsmentioning
confidence: 75%
“…The above authors also showed that despite the unstable and evolutionary nature of the complicated flow pattern, the free convection correlations for a vertical flat plate with constant temperature gives an encouraging prediction for the global Nusselt number values for the buoyancy-induced flow (Dweik, et al, 2009a). Atkins and Kanjirakkad (Atkins & Kanjirakkad, 2014) conducted measurements in the same multiple cavity rig as (Alexiou, 2000;Long, et al, 2007) but this time with a stationary shaft and the direction of flow through the rig reversed compared to the previous builds. Additionally, in these experiments the shroud was radiantly heated.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…(Apart from those on the cob surfaces, the differences between the two sets of temperature were smaller than the uncertainty in the measured values.) Table 1 shows the main parameters and average Nusselt numbers for the 19 test cases of Atkins and Kanjirakkad [12]. For each of the four approximate Rossby numbers, the cases are presented in order of ascending Grashof number.…”
Section: Experimentally Derived Nusselt Numbers and Disc Temperaturesmentioning
confidence: 99%
“…The geometry of the disc, which is shown in Figure 6, is based on the experimental Sussex rig described in [12]. The thermal conductivity, , of the titanium disc and the finite-difference equations used for the numerical solution of Equation (33) are given in [4].…”
Section: Modelled Disc Temperaturesmentioning
confidence: 99%